Investment in broadband infrastructure under local deregulation: Evidence from the UK broadband market - Nadine Fabritz; Oliver Falck (International Telecommunications Society (ITS), 2013)
This paper investigates telecommunication operator investment in broadband infrastructure after local deregulation of the wholesale broadband access market. Using a panel dataset covering all 5,598 exchange areas in the United Kingdom, we exploit regional differences in deregulation following a 2008 reform. Controlling for initial conditions, first-difference estimates show that local deregulation increases local investment in infrastructure by both the incumbent and competitors.
Keywords: L50; L96; 330; Telecommunication; Regulation; Infrastructure Investment; Wholesale Broadband Access; United Kingdom